Budaya Kuliner Tionghoa Peranakan di Kota Surakarta Pada Awal Abad Ke-20 - Gutomo, Arya (Siginjai: Jurnal Sejarah, 2023)
The beginning of the twentieth century, the city of Surakarta underwent a modernization process that led to economic and political stability. As a result, the city experienced growth in the fields of economy, infrastructure, communication, education, industrialization, and bureaucracy. This modernization was also followed by the Chinese community who immigrated from mainland China. This Chinese community brings new culture from China, one of which is culinary. Many peranakan culinary delights in the city of Surakarta have undergone changes and adjustments. Cultural adaptation allows foreign culture to adapt to local culture. This research was made by historical research methods that include (1) the determination of themes; (2) collection of sources and data (heuristics); (3) criticism (verification); (4) interpretation; and (5) historical writing (historiography). From the research conducted, it was obtained the conclusion that the Peranakan cuisine can be widely accepted by the local (Javanese) community in Surakarta City.